Amniotic membrane transplantation and trabeculectomy in a patient with pseudophakic bullous keratopathy - Imam Tiharyo, Imam Tiharyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Objective: To report the success of amniotic membrane transplantation combined with trabekulectomy ina patient with Pseudophakic bullous keratopaty.Case Report: Amniotic membrane transplantation and trabeculectomy followed by tarsoraphy had been successfully performed in an eye of male patient 67 years old with pseudophakic bullous keratopathy, with increased intraocular pressure, the visual acuity for both eyes was hand movement, intraocular pressure in the right eye was 25 mmHg and 18 mmHg in the left eye. Patient felt painful in both eyes also. Pre surgical and post surgical medication with oral and eye drop antibiotic, oral and eye drop steroid, and oral vitamin was given.Result: The painful of both eyes disappeared on the            111 day after amniotic membrane transplantation and no recurrence in 2 week observation. In the right eye amniotic membrane dissolves on the 41n day after surgery, an epithelization occurred on the 51" day after surgery. On the 7th day the visual acuity was 2/60. Amniotic membrane dissolves on the 31d day in the left eye, epithelization occurred on the 4th day. On the 71h day the visual acuity reached 3/60 and remained constant until the 2"tl week of observation.Conclusion: Amniotic membrane transplantation followed by tarsoraphy is effective for pseudophacic bullous keratopathy treatmentKey words: Pseudophacic - bullous keratopathy - amniotic membrane transplantation- trabeculectomy-intraocular pressure- visual acuity-